Clinical Course of Untreated and Treated Chronic Hepatitis B in Pregnant Patients: A Prospective Study - Yasemin Nadir; Ayse Batirel; Ayse Yasemin Karsidag; Fatma Kaya Narter; Ahmet Nadir (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Implementation of strategies to prevent vertical transmission is highly important steps in reducing the global burden of chronic hepatitis B. We conducted this prospective study to observe the clinical course and outcomes of untreated and treated HBV in pregnant.